Farmers’ Problem Confrontation in Organic Farming at Magura Sadar Upazila of Bangladesh - Biswas, Soumitro; Islam, Md Matiul (South Asian Journal of Agriculture, 2019)
The purpose of the study was to determine the problems confronted by the farmers in organic farming and to explore the relationship between the selected characteristics of the farmers and their problem confrontation in organic farming. A number of 24 problems in organic farming were selected. The 12 characteristics of the respondents were selected. Data were collected from randomly selected 61 farmers using a pre-tested interview schedule during January 5 to March 20, 2018. Majority (70.5%) of the respondents belonged to medium problem confrontation category, while 29.5% of the respondents fall in high problem confrontation category related to organic farming. A Problem Confrontation Index (PCI) was used to make comparison among the 24 selected problems. On the basis of PCI lack of knowledge on organic farming ranked first which is followed by lack of own poultry and livestock, very less production per unit area, while low accessibility of land due to share cropping ranked as the last confronted problem. Spearman's Rank Order Correlation was used to ascertain the relationship between the focus variable and personal characteristics of the respondents. Among the twelve selected characteristics of the farmers, educational qualifications and extension contact showed negative significant relationship with their problem confrontation in organic farming. The remaining characteristics showed no significant relationship with their problem confrontation. This meant that the farmers having more education and extension media contact were likely to have lesser problem confrontation in organic farming. South Asian J. Agric., 7(1&2): 19-24